Surgical Team Radiation Exposure from C-arm during Orthopedic Surgical Procedures - Almanie, Ahlam; Shima Seneysel Bachari (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: A C-arm device for accurate and better results during orthopedic surgeries seems essential. According to the linear carcinogenic model, exposure to X-rays can increase the risk of malignancy. Due to the lack of monitoring of hospitals in the region, we decided to measure the radiation exposure of the orthopedic surgery team. Methodology: This descriptive cross-sectional study was conducted at Abadan Shahid Beheshti Hospital between August and October 2020 with prior ethical committee approval. All the participants fill out the consent form before participating in the study. The census gave twenty thermoluminescence dosimeters to the orthopedic surgery team. They were asked to place the dosimeters on the chest on their cover and use them in orthopedic surgeries for three months. Also, a questionnaire was distributed among the employees, and they were asked about the number of operations they attended and how long they were in the operating room Result: The average annual dose received by the entire surgical team was 0.24 mSv, significantly differing from the annual limit. (P < 0.001). Conclusion: Even though the dose absorbed by the surgical team is less than the limits set by ICRP due to the carcinogenicity of even small amounts of radiation, the observance of protective principles is still recommended. Also, the surgery team involved in C-arm procedures should be controlled with monitoring tools such as TLD dosimeters. Keywords: Thermoluminescence dosimeters, C-arm, Occupational exposure, X-ray, Radiation protection, Orthopedic surgery